Analisis Algoritma Convolutional Neural Network (CNN) untuk Pengenalan Pola Tangan Berdasarkan Citra Garis Telapak Tangan - Fazila Nazifa Edilia; Lailan Sofinah Harahap; Andita Utami; Zianah Nafisah Simbolon (Cosmic Jurnal Teknik, 2026)
Individual identification is an important aspect of security and biometric authentication systems. One biometric characteristic with high potential is palm print patterns, as each individual has a unique pattern that is difficult to forge. Therefore, it is necessary to develop an individual identification system based on palm print images using a pattern approach with the Convolutional Neural Network (CNN) method. Test results show that this method is capable of identifying individuals with a fairly high level of accuracy, depending on the image quality and training parameters as well as the network architecture used.